Pengaruh Partisipasi Anggaran, Pemberian Reward, Dan Asimetri Informasi Terhadap Budgetary Slack (Studi Empiris Pada Hotel Berbintang Di Kabupaten Gianyar) - Komang Putriyani; Gede Adi Yuniarta (Universitas Pendidikan Ganesha, 2021)
The study aims to prove the effect of budget participation, reward and information asymmetry on budgetary slack at star hotels in Kabupaten Gianyar. This type of research is quantitative research. The sampling technique in this study was purposive sampling. Data were tasted on SPSS 24 and analyzed using descriptive analyzed using descriptive analysis and multi linear regression analysis.The results showed that the significance value of the budget participation variable was 0,000, the reward was 0,000 and the information asymmetry was 0,000 (0,05). So budget participation, rewarding and information asymmetry have a positive and significant effect on budgetary slack. This shows that with budget participation, providing rewards and information asymmetry, it can affect the budgetary slack in a company or organization in hotels throughout the Gianyar regency.